Avaliação do perfil de resposta imune e da expressão dos receptores P2X7, P2Y11 e A2A na forma indeterminada da doença de Chagas - Souza, Viviane do Carmo Gonçalves (2016)
Most infected individuals by protozoan Trypanosoma cruzi is in the indeterminate form of Chagas disease (IFCD), which is characterized by the presence of a tissue inflammatory infiltrate composed by mononuclear cells which proliferate and produce pro and anti-inflammatory cytokines, even in the absence apparent morbidity. Inflammation resulting from cellular immune activation is responsible for parasite control and tissue repair. Anti-inflammatory cytokines are important to the regulation of inflammation, preventing immunity-mediated excessive tissue damage. The importance of limiting inflammation in CD is attributed mainly to the prevention of thromboembolic events triggered by infection which leades to progression to chagasic cardiomyopathy, one of the most common causes of death by CD. Purinergic signaling, mediated by ATP and adenosine, plays an important role in immune, inflammatory as vascular responses in CD. At first the inflammation, extracellular ATP works as an endogenous pro-inflammatory and immunostimulatory mediator through the activation of P2X7 receptor in the damaged cells microenvironment. On the other hand, P2Y11 and A2A receptors induce inhibitory effects mediated by ATP and adenosine, respectively, in different immune cells. The profile of serum cytokines involved in Th1, Th2 and Th17 responses was analysed by flow cytometry in order to determine the microenvironment generated by the infection during IFCD, in a study of the case-control. Considering the importance of purinergic receptors to the propagation of ATP and adenosine paracrine and/or autocrine signaling in the immune system, the expression of P2X7, P2Y11 and A2A receptors were evaluated by Real time-CRP in lymphocytes from IFCD patients (n=12) and apparently healthy subjects (control group, n=18) as well as cellular permeability induced by ATP-mediated P2X7R activation. The results showed that the serum levels of IL-2, IFN-ᵧ, IL-17 and IL-10 were not altered in patients with IFCD in relation to control group (P>0.05). However, a positive correlation was observed between TNF-α and IL-10 as well as between IFN-ᵧ and IL-4 showing a regulation of the inflammatory response during IFCD. A significant decrease in the TNF-α/IL-10 ratio was found (P<0.05), demonstrating the presence of a favorable response to control mechanisms of inflammation in IFCD patients. This result is based on the low concentrations of TNF-α in the serum from IFCD patients possibly as a result of high levels of IL-6 which would contribute to the maintenance of an anti-inflammatory response. The balance between Th1/Th2 responses was evaluated through the IFN-ᵧ/IL-4 ratio which was shown to be decreased in IFCD patients (P<0.05), favorable to IL-4 production, establishing a predominance of a Th2 response. While the gene expression of both P2X7R and P2Y11R and the cell permeability to P2X7R did not present significant changes, lower levels of A2AR gene expression in lymphocytes of IFCD patients were statistically observed (P<0.05). Together, these results suggest that an anti-inflammatory microenvironment negatively modulates the signaling pathway mediated by A2AR in lymphocytes so as to limit the immunosuppression induced by high levels of extracellular adenosine. Therefore, the adenosinergic signalling appears to play an important role in the regulation of imune, inflammatory and vascular responses in IFCD, contributing to the host-parasite balance and to control of clinical course of CD.